University Physics Volume 1 - Sanny, Jeff; Ling, Samuel; Open Textbook Library (Open Textbook Library, 2016)
University Physics is a three-volume collection that meets the scope and sequence requirements for two- and three-semester calculus-based physics courses. Volume 1 covers mechanics, sound, oscillations, and waves. This textbook emphasizes connections between between theory and application, making physics concepts interesting and accessible to students while maintaining the mathematical rigor inherent in the subject. Frequent, strong examples focus on how to approach a problem, how to work with the equations, and how to check and generalize the result.
PrefaceUnit 1. Mechanics -- Chapter 1: Units and Measurement -- Chapter 2: Vectors -- Chapter 3: Motion Along a Straight Line -- Chapter 4: Motion in Two and Three Dimensions -- Chapter 5: Newton's Laws of Motion -- Chapter 6: Applications of Newton's Laws -- Chapter 7: Work and Kinetic Energy -- Chapter 8: Potential Energy and Conservation of Energy -- Chapter 9: Linear Momentum and Collisions -- Chapter 10: Fixed-Axis Rotation -- Chapter 11: Angular Momentum -- Chapter 12: Static Equilibrium and Elasticity -- Chapter 13: Gravitation -- Chapter 14: Fluid Mechanics -- Unit 2. Waves and Acoustics -- Chapter 15: Oscillations -- Chapter 16: Waves -- Chapter 17: Sound -- Appendix A: UnitsAppendix B: Conversion FactorsAppendix C: Fundamental ConstantsAppendix D: Astronomical DataAppendix E: Mathematical FormulasAppendix F: ChemistryAppendix G: The Greek AlphabetIndex
In English.
Description based on online resource
Keywords: Science -- Textbooks; Physics -- Textbooks